The socioeconomic vulnerability of coastal communities to abrasion in Samas, Bantul Regency, Indonesia - Choirunnisa, Audi Karina; Giyarsih, Sri Rum (Quaestiones Geographicae, 2018)
This research was conducted in Srigading and Gadingsari Villages, Samas District, Bantul Regency, the Special Region of Yogyakarta. Both of these villages were selected as the study area because of their high vulnerability to coastal erosion. This research aimed to analyse the physical, social, and economic vulnerability and the capacity of communities in both villages to deal with erosion in Samas Coast using primary and secondary database. According to the results of the physical and socioeconomic scenarios, Srigading has a high vulnerability level, whereas Gadingsari has a low vulnerability level. Meanwhile, the equal scenario results in the same spatial distribution of vulnerability as the aforementioned scenarios. This research also finds that the capacity, which was based on knowledge of coastal erosion and its risk reduction measures, is categorized as medium. This capacity level is shaped by the constantly improved preparedness as communities experience coastal erosions directly.